Electrical behaviors of (1-x)BZT07-xBNWT lead free solid solution binary system - Gobwute Rujijanagul (2018)
Solid solutions of the (1-x)Ba(Zr 0.07 Ti 0.93 )O 3 -xBa((Ni 0.5 W 0.5 ) 0.1 Ti 0.9 )O 3 system with 0.05 ≤ x ≤ 0.2, were fabricated via a solid-state reaction technique. All samples exhibited a pure phase perovskite structure. The x = 0.05 samples exhibited very high dielectric constants ( > 60,000) for temperatures over 400°C, while the x = 2.0 samples had a higher degree of dielectric constant stability over a wide temperature range. The ceramics also showed a dielectric relaxor behavior. The frequency dependence of the loss tangent peak was observed to follow an Arrhenius law where the activation energies increased with increasing Ba((Ni 0.5 W 0.5 ) 0.1 Ti 0.9 )O 3 content. The result suggests that the addition of Ba((Ni 0.5 W 0.5 ) 0.1 Ti 0.9 )O 3 has strong effects on the properties this ceramic system. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.